Coordination-Induced Band Gap Reduction in a Metal-Organic Framework - Peeples, Craig A.; Cetinkaya, Ahmet; Tholen, Patrik; Schmitt, Franz-Josef; Zorlu, Yunus; Yu, Kai Bin; Yazaydin, Ozgur; Beckmann, Jens; Hanna, Gabriel; Yucesan, Andog (WILEY-V C H VERLAG GMBH, 2022)
Herein, we report on the synthesis of a microporous, three-dimensional phosphonate metal-organic framework (MOF) with the composition Cu-3(H-5-MTPPA)(2) . 2 NMP (H-8-MTPPA=methane tetra-p-phenylphosphonic acid and NMP=N-methyl-2-pyrrolidone). This MOF, termed TUB1, has a unique one-dimensional inorganic building unit composed of square planar and distorted trigonal bipyramidal copper atoms. It possesses a (calculated) BET surface area of 766.2 m(2)/g after removal of the solvents from the voids. The Tauc plot for TUB1 yields indirect and direct band gaps of 2.4 eV and 2.7 eV, respectively. DFT calculations reveal the existence of two spin-dependent gaps of 2.60 eV and 0.48 eV for the alpha and beta spins, respectively, with the lowest unoccupied crystal orbital for both gaps predominantly residing on the square planar copper atoms. The projected density of states suggests that the presence of the square planar copper atoms reduces the overall band gap of TUB1, as the beta-gap for the trigonal bipyramidal copper atoms is 3.72 eV.
Keywords: Density of States; Ligand Design; Metal-Organic Framework (MOF); Solvothermal Synthesis; Surface Area; ELECTRICAL-CONDUCTIVITY; PLATFORM; SOLIDS; FUNCTIONALIZATION; CHEMISTRY; DESIGN; CARBON